DETERMINACIÓN DE PARÁMETROS NUCLEARES MEDIANTE LAS TÉCNICAS DE CINÉTICA INVERSA Y RUIDO NEUTRÓNICO - Zapata B., Magaly (2004)
A measuring system of nuclear parameters using the techniques of In verse Kinetics and Neutron Noise has been installed in the Peruvian Nuclear Resean:h Reactor RNl. In this papera brief description of the system components is presented as well as of its ínstallatlon in the reactor core. The resu1ts of the measurements of reactor power and reactivity are reported.